(untitled) (Research, Society and Development, 2022)
Introduction: Gestational monitoring is present in the public health network, bringing pregnant women closer to multidisciplinary teams, which focus attention on preventing problems in pregnancy. Objective: To evaluate how dental prenatal care is being carried out in the city of Caicó-RN, based on the vision of the service user and the dentist. Methods: Exploratory qualitative research. We sought to assess the knowledge of pregnant women and dentists about oral health care for pregnant women at the FHS in the interior of Rio Grande do Norte, through the application of an online instrument via Google Forms for both groups, containing socioeconomic data, information on the perception of dental and specific prenatal care in the professional area. Results: The professional who attended most prenatal consultations in the last pregnancy of the present study, it was seen that the doctor appears in 66.7% of the cases, followed by the nurse with 33.7%. 77.8% of pregnant women responded that they performed dental prenatal care in basic health units and hospitals. 100% of the professionals participating in the survey stated that they have knowledge about dental prenatal care and the pathologies most commonly found in the clinical routine with pregnant women were periodontal diseases (77%), followed by caries (66%) and periodontal abscess (11%). %). Conclusion: There is still resistance on the part of pregnant women to perform the care and little representation of dentists in health services. However, the degree of knowledge about dental prenatal care and the experience of the professionals participating in the study were satisfactory.